Review of Human Resources Management - Mohanty, Sasmita; Pradhan, Bibhuti Bhusan (International Journal of Psychosocial Rehabilitation, 2019)
Research acknowledges that there cannot be a High Performance Organization (HPO) without a great value on human resource management (HRM) and human resource development (HRD). Although, there is not always been complementary pairing between HRM and HRD. HRD’s evolution from its roots in the transfer of human understanding to HRM and current HRD activities reveals that environmental, social, and political impacts have increased the need for institutions to focus on employee growth in the areas of flexibility, innovation, and capacity. Over the last decade, skill-based human resources (HR) management work has grown considerably. Over this time, researchers have taken a closer look at each of the major HR roles to learn more about how specific types of HR policies, processes and procedures can affect a wide range of outcomes at the employee and firm level. The following analysis shows the importance of HRM and HRD to the leadership of the organizations. In addition, the research being examined builds a close association between the attributes of an HPO and the skills being transferred through effective collaboration between HRM and HRD